An Analysis of Chinese Commercial Banks Performance during 2013-2017: the Cost Efficiency and Profitability Determinants - ZHANG, YAO (2018)
While China's economy has grown rapidly, China's banking industry has become the research object of many scholars in the world. This paper will assume this as a starting point to try to explore China's banking industry. The purpose is to practice the Stochastic Frontier Analysis (SFA) approach and the system Generalized Method of Moments (SGMM) approach to investigate the performance of Chinese commercial banks through the cost efficiency and the determinants of their profitability. The models employ unbalanced dynamic panel data from 200 commercial banks during five years in which 2013 to 2017. The paper first presents the development process and reform measures of the Chinese banking industry for nearly 40 years since the reform and opening up in 1978. After that, the past research on these two directions will be reported in the next section. In the third principal chapter, both the SFA model and SGMM model, as well as variables selection, will be described in detail. Subsequently, the estimation of cost efficiency will be compared and analysed from two aspects, namely, these commercial banks with different ownership and different economic regions. Also, the determinants affecting bank profitability will be divided into bank-specific factors and macroeconomic factors and will illustrate how they influence bank profitability based on the empirical results. Finally, in the conclusion section, several recommendations for the research findings and the policy implications will be performed and targeted.